ANTECEDENTS AND CONSEQUENCES OF IMPULSE BUYING BEHAVIOR - Renny Risqiani (Business and Entrepreneurial Review, 2015)
The objective of this research is to identify and analyze the factors that of influence of consumers The purpose of this research is to analyze and determine the factors that influence consumer’s impulse buying behavior in mini market (convenience store) based on influence of variable store atmosphere, in-store browsing, in-store layouts, salesperson, promotional approach, reference group, use payment card and shopping emotion. This study attempts to analyze post-purchase consumer regret and investigates the influence of impulse behavior to post purchase regret.The sample was collected and analyzed from 244 respondents of convenience store shoppers in ages in Greater Jakarta region. Structural Equation Modeling (SEM) and AMOS were used for data analysis and hypotheses testing.Results indicate that there is a significant effect of the impulse buying behavior in the four variables; the role of salesperson, sales promotion, the participation of reference groups and payments made by debit card. As a result, this study addresses concerns about disappointed consumers after making an impulsive purchase.This study emphasizes the importance of friendly and ready to help the consumers in sales person’s role to encourage consumers to make impulsive purchases. The readiness and friendliness of employees in serving consumers can occur when companies often provide training to employees.Employees must pay particular attention and effort put into effect reward and punishment system that can increase work motivation. Furthermore, reference groups have an effect on impulsive buying behavior, and the tendency of consumers to shop more is high when accompanied with a mutual friend. In addition to sales person and reference group, promotions made by the store can also attract consumers and encourage them to make purchases impulsively. Additional value that can encourage the purchase of impulsive payment system is by using a debit card instead of credit card. In further research, the convenience store consumers do not make purchases in large quantities so payment using credit card does not give a significant effect while consumers can use a debit card in lieu of cash. Other research results show consumers regret after making an impulsive purchase. The negative consequence of consumer disappointment is that consumers become disloyal even spreading negative word of mouth. Thus, the company needs to explore these impacts in more detail and determine the factors that can reduce consumer disappointment This study examines the factors that cause and impact impulse buying behavior. The study was conducted at convenience stores in Greater Jakarta region. The results showed the impact of impulse buying behavior on consumer regret after doing impulse buying.